‘Looking for the tombs of dragons’: preliminary results of archaeo-geochemical prospecting studies at Tirinkatar - Karmir Sar area, southern slopes of Mt Aragats, Armenia - Hovhannisyan, Arshavir; Arakelyan, Dmitri; von der Osten, Harald; Hnila, Pavol; Gilibert, Alessandra; Siradeghyan, Varduhi; Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
An interdisciplinary archaeogeochemical research on vishaps (stone stelae also known as dragon stones) has been carried out for the first time in Armenia. The survey area is situated in the neighborhood of Tirinkatar and Karmir Sar volcanoes on southern slopes of Mt. Aragats. The geochemical prospecting studies have been realised on a high mountain meadow (2850 m asl) with 12 vishaps and numerous circular stone structures known as cromlechs. Five cromlechs excavated until now did not yield any human remains and the main aim of the geochemical prospection was to check whether other cromlechs detected by archaeological surface survey and by ground-penetrating radar contained burials. The geochemical haloes of some chemical elements indicate their anthropogenic character and a very high probability that some of the cromlechs were tombs.